A review of standardized high-throughput cardiovascular phenotyping with a link to metabolism in mice - Jiri Lindovsky; Zuzana Nichtova; Nathalia R. V. Dragano; David Pajuelo Reguera; Jan Prochazka; Helmut Fuchs; Susan Marschall; Valerie Gailus-Durner; Radislav Sedlacek; Martin Hrabě de Angelis; Jan Rozman; Nadine Spielmann (Mammalian Genome, 2023)
Cardiovascular diseases cause a high mortality rate worldwide and represent a major burden for health care systems. Experimental rodent models play a central role in cardiovascular disease research by effectively simulating human cardiovascular diseases. Using mice, the International Mouse Phenotyping Consortium (IMPC) aims to target each protein-coding gene and phenotype multiple organ systems in single-gene knockout models by a global network of mouse clinics. In this review, we summarize the current advances of the IMPC in cardiac research and describe in detail the diagnostic requirements of high-throughput electrocardiography and transthoracic echocardiography capable of detecting cardiac arrhythmias and cardiomyopathies in mice. Beyond that, we are linking metabolism to the heart and describing phenotypes that emerge in a set of known genes, when knocked out in mice, such as the leptin receptor ( Lepr ), leptin ( Lep ), and Bardet–Biedl syndrome 5 ( Bbs5 ). Furthermore, we are presenting not yet associated loss-of-function genes affecting both, metabolism and the cardiovascular system, such as the RING finger protein 10 ( Rfn10 ), F-box protein 38 ( Fbxo38 ), and Dipeptidyl peptidase 8 ( Dpp8 ). These extensive high-throughput data from IMPC mice provide a promising opportunity to explore genetics causing metabolic heart disease with an important translational approach.